ELECTORAL FRAUD AS AN OBSTACLE TO DEMOCRACY STABILIZATION: A SYSTEMATIC LITERATURE REVIEW - Sabilah, Ammaya; Nurjaman, Asep (Fakultas Politik Pemerintahan, 2024)
The research is aimed at identifying the current electoral fraud that, in this study, is believed to disrupt the stability of the most democratic states from 2019 to 2024. The research method used in this study is a systematic literature review based on the use of 269 scientific articles sourced from the Scopus database that have been organized and restricted according to the context of related topics. The article review process was carried out using the Vosviewer application. Of the 269 scientific articles on electoral fraud that have been processed, it was revealed that from 2019 to 2024, there has been a decline in the interest in research on electoral fraud, which can be proved by the number of articles that are less stable in the scopus database. The results of this research have contributed to the development of political science that specifically deals with various electoral fraud practices. The research has the limitation that the data analyzed only comes from the Scopus database, so the findings of this study cannot comprehensively describe electoral fraud studies around the world. Further research needs to be balanced with the use of scientific articles, which are not only sourced through the Scopus database but also from internationally renowned databases such as the Web of Science and Dimensions Scholars.